Force-based seismic design of mixed CLT/Light-Frame buildings. (1st August 2018) - Follesa, M.; Fragiacomo, M.
Highlights: A literature review on the seismic design of mixed structures is presented. Non-linear analyses are carried out for several layouts of CLT and Light-Frame walls. A formulation for the behaviour factor q of Light-Frame/CLT buildings is proposed. A discussion on the methods to evaluate the stiffness of LF and CLT walls is made. The validity of the formulation is finally checked via non-linear dynamic analysis. Abstract: This paper presents the results of a numerical study aimed to investigate the seismic behaviour of mixed multi-storey wood buildings made of CLT and Light-Frame shear walls acting at the same level. Eurocode 8 provides little information on the seismic design of buildings with different lateral load resisting systems working at the same level. A suggestion is given to perform non-linear static or non-linear dynamic analysis to design the structure. The application of linear analysis methods using the force-based procedure is not possible since the value of the behaviour factor q of the mixed system is unknown. The aim of this investigation is to propose a simple analytical formulation to estimate the value of the q-factor of the mixed system, so as to enable the use of the force-based philosophy of Eurocode 8 for the seismic design of mixed CLT/Light-Frame buildings. This was achieved by analysing the results of non-linear dynamic (time-history) analyses performed on a four-storey case-study building with different combinations of CLT and Light-Frame shear walls. Finally, the validity of the proposed formulation is checked by means of non-linear dynamic (time-history) analyses performed on the same four storey case-study building in one of the hybrid combinations of CLT and Light-Frame shear walls.